Acceptance of COVID-19 Vaccine Among Undergraduate Students - Abid, Muhammad Ali; Buzdar, Muhammad Ashraf; Junejo, Shizma; Karim, Nasim (Pakistan Armed Forces Medical Journal, 2023)
Objective: To assess the acceptance of the COVID-19 vaccine among medical and non-medical undergraduate students and compare the COVID-19 vaccine receptivity differences between medical and non-medical undergraduate students. Study Design: Cross-sectional study. Place and Duration of Study: Bahria University Medical & Dental College, and Bahria University Karachi Campus Pakistan, from Mar to Jun 2021. Methodology: In this study, a total of 392 participants, were selected by non-probability convenience sampling. Students aged 19-26 years were enrolled. Participants were required to sign a voluntary consent form prior to participation. The questionnaire included 21 questions inclusive of demographic characteristics, insight regarding COVID-19 disease, prior EPI vaccine exposure, attitude towards COVID-19 vaccine, including the importance of vaccine to end the pandemic, acceptance of vaccine along with reasons and non-acceptance and sent by email as a Google form to participants. Results: There were 171(43.6%) males and females 218(55.6%). The mean age of participants was 20.7±2.29 years. 217(55.4%) students were from the MBBS programs, and 175(44.6%) were from non-MBBS programs. COVID-19 vaccine acceptability was better amongst medical students, with 182(83.9%) considering it safe for use in contrast to 5(2.8%) non-medical students who considered it safe. Conclusion: The comparison of knowledge and attitudes towards accepting the COVID-19 vaccine between medical students and non-medical students revealed better acceptance amongst undergraduate medical students than non-medical undergraduate students.